Pengaruh Penggunaan Model Pembelajaran Problem Based Learning Berbantuan Fishbone Dalam Meningkatkan Keterampilan Proses Sains Siswa - Kurniati; Sri Wahyuni; Sitti Asmah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to understand the influence of Problem-Based Learning model assisted by Fishbone in developing science process skills on learning outcomes of 10th-grade students at SMA Negeri 12 Bone. The population of the research was all 10th-grade students at SMA Negeri 12 Bone, with the research sample selecting one class, specifically all students in class X6 totaling 35 students. Data collection techniques involved distributing questionnaires and documentation. The research type was a pre-experimental design using the